Sexual harassment and misconduct: an encyclopedia - Robertiello, Gina (ABC-CLIO, 2021)
"This authoritative reference work informs readers about the scope, nature, and prevalence of sexual harassment and misconduct in all walks of American life, and how changes in policy, law, and traditional gender dynamics can address the problem"--